Agreement on Agriculture WTO: Discourse on Indonesia's Food Security in a Global Context - Akbar Kurnia Putra; Muhammad Reza Syariffudin Zaki; Bernard Sipahutar; Hanna Adistyana Hefni; Christopher Michael Cason (Universitas Negeri Semarang, 2024)
This article evaluates Indonesia’s progress towards its national goal of food security. To meet the Indonesian population’s right to food by formulating national policies and supporting regulations on agriculture for food sovereignty while conducting economic diplomacy utilizing its membership in the WTO Agreement on Agriculture and the G33 coalition. Normative juridical research and comparative legal analysis examine provisions concerning agriculture in Indonesia’s national legal instruments and WTO’s Agreement on Agriculture. The article finds that Indonesia has failed to attain either food security or food sovereignty, postponed by international negotiations where developed countries object to the developing and least-developed countries’ Special Products and Special Safeguard Mechanism. The provisions are imperative for supporting Indonesia’s economic growth to attain food security and eradicate poverty, considering the significant gap between developed and developing economies. This article suggests that Indonesia strengthen its bilateral economic relations with influential, more economically developed members of the WTO agreement to garner international support to meet national food security and exercise Indonesia’s right to regulate within its jurisdiction, leading to food sovereignty.